Anabolic steroid use in adolescents: Identification of those at risk and strategies for prevention - Mulcahey, M. K.; Schiller, J. R.; Hulstyn, M. J. (The Physician and Sportsmedicine, 2010)
Success in sports is often defined by winning, which drives athletes to use performance-enhancing drugs (PEDs) to gain an advantage over opponents. Over the past 20 years, use of PEDs by Olympic and professional athletes has led to public discussion regarding potential negative health effects and ethical implications of their use. Unfortunately, PEDs are not isolated to professional athletes, as PED use in adolescents has increased dramatically. Many professional organizations, including the American Academy of Orthopaedic Surgeons (AAOS), have taken a stance against PED use in sports. The AAOS believes neither anabolic steroids nor their precursors should be used to enhance performance or appearance, and that these substances should be banned in all sports programs. Pediatricians and orthopedists are often the first physicians to see these young athletes. It is critical for these physicians to recognize the significance of the problem, have the knowledge to inform adolescents, dissuade them from future use, and provide viable alternatives for meeting performance goals.